1-123-Iodo-α-methyl tyrosine SPECT in non-parenchymal brain tumours - Matheja, P.; Weckesser, M.; Rickert, Ch.; Franzius, Ch.; Palkovic, St.; Riemann, B.; Schober, O. (Nuklearmedizin - NuclearMedicine, 2002)
Purpose: Scintigraphy using I-123-iodo-α-methyl tyrosine (IMT) is useful in the preoperative characterization of gliomas, in detecting recurrent glioma and in the biological re-evaluation of residual or recurrent tumours. A systematic evaluation of non-parenchymal brain tumours has not yet been performed. The aim of the present study was to evaluate IMT SPECT in the management of intracerebral metastases and lymphomas. Patients and methods: IMT uptake was analyzed in 31 patients with 28 metastases of extracerebral solid tumours and 7 cerebral lymphomas. Histology revealed high grade lymphomas, melanomas, and carcinomas of the following origin: lung, unknown primary, breast, colon, renal cell, ovary, vagina, frontal sinus. IMT uptake was quantified as ratio between maximal tumour accumulation and average uptake in the contralateral hemisphere. Results: All tumours except two renal cell and one small cell lung carcinoma metastases accumulated IMT (91%). The highest IMT uptake was found in a metastasis of lung carcinoma. IMT uptake was highly variable and was similar in primary and in recurrent tumours. Conclusion: Significant accumulation of IMT is seen in the majority of tumours, so that this technique might be helpful for the management of cerebral metastases and lymphomas.
Keywords: Brain tumour; SPECT; I-123-iodo-α-methyl tyrosine; metastasis; lymphoma